2018
DOI: 10.1029/2017wr022021
|View full text |Cite
|
Sign up to set email alerts
|

Salt Dynamics in Coastal Marshes: Formation of Hypersaline Zones

Abstract: Salt is a key solute in salt marshes and under the influence of evapotranspiration can accumulate to a high concentration level in the marsh soil and precipitate in the solid form to become a significant stressor for plants, affecting marsh plant productivity and ecological zonation. Numerical simulations of coupled pore water flow and salt transport were conducted to examine how spring-neap tides and evaporation combine to influence salt dynamics and distribution patterns in marshes. The salt pan formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 69 publications
1
50
1
Order By: Relevance
“…Recently, intensive studies were conducted to examine surface water and groundwater interactions in creek-marsh systems subjected to tides (Adams, 1963;Cao et al, 2012;Moffett et al, 2012;Shen et al, 2018;Ursino et al, 2004;Wilson and Gardner, 2006;Xiao et al, 2017;Xin et al, 2013). They demonstrated a near-creek pore-water circulation, in which water infiltrates from the marsh platform during flood tides and seeps out of the creek bank and bottom during ebb tides (Cao et al, 2012;Wilson and Gardner, 2006;Xin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, intensive studies were conducted to examine surface water and groundwater interactions in creek-marsh systems subjected to tides (Adams, 1963;Cao et al, 2012;Moffett et al, 2012;Shen et al, 2018;Ursino et al, 2004;Wilson and Gardner, 2006;Xiao et al, 2017;Xin et al, 2013). They demonstrated a near-creek pore-water circulation, in which water infiltrates from the marsh platform during flood tides and seeps out of the creek bank and bottom during ebb tides (Cao et al, 2012;Wilson and Gardner, 2006;Xin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As an example of a study based on groundwater mechanics, Kashef (1983) used the Ghyben-Herzberg relationship to demonstrate that the seawater wedge reached far inland. This was further confirmed by the 2-D numerical model constructed by Sherif et al (1988), who concluded that the width of the dispersion zone may be considerable. Sefelnasr and Sherif (2014) showed the sensitivity of the area to sea-level rise with a 3-D numerical model, as the low topography of the Nile Delta allowed for a far-reaching land surface inundation that can be detrimental to freshwater volumes (Ketabchi et al, 2016;Kooi et al, 2000).…”
Section: Introductionmentioning
confidence: 56%
“…Hydrogeological research dealing with this area generally assumed that the connection between aquifer and sea is completely open (e.g. Kashef, 1983;Mabrouk et al, 2018;Sefelnasr and Sherif, 2014;Sherif et al, 1988), but there exists ample evidence against this assumption from both seismics (Abdel-Fattah, 2014;Abdel Aal et al, 2000;Samuel et al, 2003) as well as from the fact that offshore borelogs contain more clay than sands (Salem et al, 2016). These observations can be explained by the fact that the fraction of marine clays in deltas generally increases seawards (Nichols, 2009).…”
Section: Hydrogeologymentioning
confidence: 99%
See 1 more Smart Citation
“…7 and 8), after which they reach equilibrium conditions until the next time slice. This may seem very rapid, but experiments with smaller scale models which fully accounted for salt precipitation and dissolution, evapo-concentration, variable-density groundwater 5 flow and the unsaturated zone, showed that higher salinities ( > 200 g/L) are possible under evaporation rates similar to those in the Nile Delta (Shen et al, 2018;Zhang et al, 2015). Given that the Late-Pleistocene sabkhas did not migrate , we deem our T-model scenarios to be conservative.…”
Section: Discussionmentioning
confidence: 99%